Theory and legal regulation of information support of administrative procedures in Ukraine - Yevhen Leheza; Iryna Odyntsova; Natalia Dmytrenko (Ratio Juris, 2021)
The article is devoted to the analysis of scientific concepts and the legal framework of the concept of information support for administrative legal proceedings. Features and peculiarities of information provision for administrative legal proceedings are studied; its differences from information support for the administrative court are stressed. The author’s definitions of the concept of information support for the administrative procedure and information support for the administrative court are proposed. Three stages of formation of national legislation regulating information provision of administrative legal proceedings are singled out. The system of laws and regulations, which provisions consolidate legal fundamentals of information support for administrative legal proceedings, is clarified. Prospective directions for the development of scientific inquiry in the field of information support for administrative legal proceedings and its legal regulation are clarified.